Floating hollow carbon spheres for improved solar evaporation - Celzard, Alain; Pasc, A.; Schaefer, Sebastien; Mandel, Karl; Ballweg, T.; Li, S.; Medjandi, G.; Nicolas; Fierro (Carbon, 2019)
Hollow carbon spheres (HCSs) were prepared from sugar alcohols encapsulated in UV-cured polymer which were hydrothermally treated in solutions of carbon precursors and carbonised at different temperatures in the presence or absence of graphitisation catalysts (Fe(III) and Ni(II)). The resultant HCSs were then spread at the surface of salt water and submitted to a solar simulator in a special ventilated chamber. The presence of HCSs floating at the surface of water was shown to increase significantly the evaporation rate compared to an HCS-free reference. The effect of carbon precursor, pyrolysis temperature, size and presence of metal was investigated and discussed. The best performances were obtained with nickel-loaded HCSs treated at 1500 °C, leading to a water evaporation rate increased by 70% with respect to the reference. These performances were discussed in terms of floatability, the latter being related to wettability, composition and apparent density of the HCSs. A model was developed for separating the contributions of floatability and thermal conductivity, definitely demonstrating that the former was the key parameter explaining the performances of floating HCSs for evaporating water submitted to a radiant heat flow.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Graphitisation; Hollow carbon spheres; Hydrothermal carbonisation; Modelling; Solar evaporation; Template method